Teach yourself visually PowerPoint 2016 - Boyd, Barbara (Freelance writer); Anthony, Ray (Teach yourself visually, 2016)
The uncomplicated PowerPoint guide designed specifically for visual learners Are you a visual learner who wants to spend more time "working on" your presentations than trying to "figure out" how to create them? "Teach Yourself Visually PowerPoint" offers you an effortless approach to creating winning presentations with the latest version of PowerPoint. This accessible resource features visually rich tutorials and step-by-step instructions that will help you understand all of PowerPoint's capabilities--from the most basic to the most advanced. With "Teach Yourself Visually PowerPoint, " you'll learn how to create slides, dress them up using templates and graphics, add sound and animation, present in a business or Internet setting, and so much more. Covering the latest additions and changes in the new version of PowerPoint, a series of easy-to-follow, full-color tutorials helps you to quickly get up and running using PowerPoint like a pro! Highly visual tutorials and step-by-step screenshots make lessons easy to follow and understand Helps you learn the basic functions of PowerPoint--and beyond Walks you through PowerPoint's latest features Demonstrates how to create memorable and captivating presentations using PowerPoint Do you prefer instructions that show you how to do something--and skip the long-winded explanations? If so, "Teach Yourself Visually PowerPoint" is for you. Provides clear, step-by-step instructions for tackling more than 150 PowerPoint 2016 tasks. Each task-based spread covers a single technique, sure to help you get up and running on PowerPoint 2016 in no time.